Implementasi Layanan Kesehatan Primer dan Komunitas yang Inklusif Disabilitas: Analisis Scoping Review - Toni Hermawan; Puput Oktamianti; Zakiah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to map and synthesize evidence on the implementation of disability-inclusive primary and community health services for persons with disabilities across various geographic contexts. This study used a scoping review design following the Arksey and O'Malley framework and JBI guidance, with literature searches conducted in Scopus, PubMed, Web of Science, and CINAHL covering the period 2021–2026, yielding 21 empirical studies selected through a staged screening process based on predefined inclusion and exclusion criteria and analyzed using a three-stage thematic synthesis approach (open coding, axial coding, selective coding). The results indicate that disability-inclusive service quality is multidimensional, encompassing eight dimensions (physical access, provider attitudes, communication, financial, participation, ethics, policy, and coordination), with barriers identified at four levels including individual (socioeconomic, disability type), interpersonal (family support), organizational (negative provider attitudes, lack of capacity), and policy (implementation gaps, inadequate funding), and access dimensions significantly impacting structural and process quality with implementation gaps as the root systemic problem. This study concludes that the integrated conceptual framework of eight dimensions of disability-inclusive service implementation produced can serve as a foundation for policy development, clinical practice, and future research agendas on health services that are truly inclusive for all persons with disabilities. Keywords: Community Health, Disability, Implementation, Primary Health Care, Service Quality